The Islamic State: a brief introduction - Lister, Charles R. (Brookings Institution Press, 2015)
Introduction: More than a Terrorist Organization 1. - 1 “Lasting and Expanding” 5. - 2 The Emerging Islamic State 25. - 3 Degrading and Destroying the Islamic State 51